2003
DOI: 10.1016/s1161-0301(03)00068-6
|View full text |Cite
|
Sign up to set email alerts
|

Input output accounting systems in the European community—an appraisal of their usefulness in raising awareness of environmental problems

Abstract: Input Output Accounting systems (IOAs) can be used to identify farming practices which are not 'environmentally neutral' and thus unlikely to be sustainable in the long term. In an EU sponsored project, European countries were surveyed and over 50 farm level IOAs identified. The subjects covered by the IOAs included nutrients, pesticides, energy, soil/habitat, conservation, wastes (e.g. packaging and tyres) and other items such as veterinary products. Nearly half the IOAs covered more than one subject and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 2 publications
0
49
0
1
Order By: Relevance
“…Previous studies have considered N balances and efficiencies more commonly than other nutrients (Goodlass et al 2003;Halberg et al 2005). This is because of the greater magnitude of N flows and surpluses at the farm scale, the lack of reliable soil N tests and the recognition of measured surplus as a quantifiable loss to the broader environment (Oenema et al 2009;Jarvis et al 2011).…”
Section: Nutrient Balances and Use Efficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have considered N balances and efficiencies more commonly than other nutrients (Goodlass et al 2003;Halberg et al 2005). This is because of the greater magnitude of N flows and surpluses at the farm scale, the lack of reliable soil N tests and the recognition of measured surplus as a quantifiable loss to the broader environment (Oenema et al 2009;Jarvis et al 2011).…”
Section: Nutrient Balances and Use Efficienciesmentioning
confidence: 99%
“…Nutrient balances have been widely adopted in the EU (Goodlass et al 2003) and USA (Koelsch 2005), and more recently, has become a compulsory requirement to supply milk in New Zealand (Sneath and Furness 2006). Although there are currently fewer pressures or incentives within Australia to determine nutrient balances, and their use is low when compared with EU, the USA or New Zealand, there is growing interest from catchment management authorities and dairy companies, as a nutrient balance is viewed as a useful tool in helping to achieve voluntary environmental nutrient management standards.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Goodlass et al (2003) identified over 45 nutrient budgeting tools currently in use in Europe. They concluded that most of the nutrient budgeting tools and documentation available did not provide assistance with interpreting outputs or changes to farm management.…”
Section: Farmer Use Of Nutrient Budgetsmentioning
confidence: 99%
“…Nutrient balances and use efficiencies could be used as key agronomic efficiency and environmental performance benchmarks to rate the performance of a farm and used as targets to encourage improvement in nutrient management (Goodlass et al 2003).…”
Section: Phosphorusmentioning
confidence: 99%